PERANAN UMPASA/UMPAMA DALAM BUDAYA BATAK TOBA TERHADAP KATEKESE DI PAROKI SANTO PAULUS ONAN RUNGGU - Lumban Tobing, Ona Sastri (STP St. Bonaventura Medan, 2021)
The enhancement of religious education within society is influenced by various factors, including culture, which plays a significant role in shaping personalities and knowledge of the Christian faith. This study aims to examine the extent of the influence of